Democratizing Knowledge: Using Wikipedia for Inclusive Teaching and Research in Four Undergraduate Classes - Pratesi, Angela; Miller, Wendy; Sutton, Elizabeth (Radical Teacher, 2019)
In four undergraduate arts-related courses taught by three faculty, undergraduate students learned how to edit Wikipedia to present authentic research to a public audience. The goal was to increase free and open access to information about women and minoritized individuals in the arts, while simultaneously facilitating the acquisition and practice of student information literacy, research, and writing skills. This article outlines the assignments for each class, summarizes the reflections of students regarding their perception of learning, and discusses the pedagogical strategies and impact of using Wikipedia editing as a research assignment. While each faculty had diverse parameters and outcomes for her respective assignment and course, overall the public nature of writing for Wikipedia and the demonstrated need for presenting the contributions of women art educators, women artists, and Haitian artists created a common motivation for students and faculty to work together as knowledge constructors.